Studies of fundamental properties of chlorophyll molecules using steady state fluorescence anisotropy and two-dimensional electronic spectroscopy - Christea,Alexander (2025)
The purpose of this study is two-fold: first to validate previous findings, that showed that the central atom in (bacterio)chlorophyll changes ligand coordination number upon being cooled at a certain rate (in certain solvents), and to resolve the Qx and Qy bands from the total absorption spectrum. We studied bacteriochlorophyll A (BChl A), bacteriochlorophyll C (BChl C), and chlorophyll A (Chl A) in 1-propanol and 2-propanol at room temperature, and at 115 K, by fluorescence measurements. We have successfully resolved the Qx and Qy bands of BChl A, BChl C and Chl A (in both solvents) and have shown that there is indeed a large spectral difference in the absorbance spectra between chromophores solvated in 1-propanol or 2-propanol (when they are cooled at a slow rate). In 1-propanol the chromophores exhibit a large band structure change accompanied by a shift of the Qx band, while in 2-propanol no such change is observed for either system in the absorbance spectra. The second part of the study was to show, through coherent two-dimensional spectroscopy (2DES) how the energy states of bacteriochlorophyll A, in a 1:1 ethanol:methanol mixture, correlate and couple to each other; whether or not there is vibronic coupling; and whether there are any population dynamics occurring between the energy states. A population decay was observed during the first 600 fs, attributed to vibrational relaxation within the Qy electronic manifold. The vibrational and vibronic coherences observed in the 2DES experiment correspond well to previous reports where vibrational modes were studied using resonance Raman (RR) spectroscopy. Coherent superposition of vibrational states were seen to oscillate with the frequencies υ1 = 560 cm-1, υ2 = 730 cm-1, υ3 = 1180 cm-1. Oscillation signals were analyzed in comparison to published theoretical predictions for model vibrational and electronic systems.
Keywords: chemical physics; ultrafast dynamics; 2DES; two-dimensional; 2D; spectroscopy; fluorescence; anisotropy; femtosecond; chlorophyll; bacteriochlorophyll